Use of Turkey Meat Affected by White Striping Myopathy for the Development of Low-Fat Cooked Sausage Enriched with Chitosan - Carvalho, Larissa Tatero; Lorenzo, Jose M.; Carvalho, Francisco Allan L. de; Bellucci, Elisa Rafaela Bonadio [UNESP]; Trindade, Marco Antonio; Dominguez, Ruben (Mdpi, 2020)
The main objective of this research was the development of a healthy meat product from turkey meat with white striping myopathy. The effect of adding different proportions of chitosan on the qualitative characteristics, sensory acceptance, and stability of cooked sausages during storage was studied. Three treatments were elaborated (control, 1.5% chitosan, and 3% chitosan), stored for 56 days, and characterized in terms of chemical composition, texture profile analysis, drip and pressure loss analysis, and sensory analysis (after processing; day 0). In the different storage periods (0 and 56 days), the pH value, color, thiobarbituric acid reactive substances (TBARS), and volatile compounds were evaluated. The results showed that the moisture content, lipids, proteins, and weight loss decreased (p < 0.05) and the ash content increased (p < 0.05) with the addition of chitosan. Similarly, the values of texture parameters (hardness, cohesiveness, gumminess, and chewiness) were higher in the sausages reformulated with chitosan than in control samples. The addition of chitosan increased the pH and yellowness (b*) values and reduced (p < 0.05) redness (a*) and lightness (L*) values. The b* values (only in reformulated sausages) and pH increased during storage, while a* showed a significant reduction after 56 storage days. Lipid oxidation (TBARS) was kept below the limits of quantification in all samples and both after processing and 56 storage days. However, when quantifying the lipid-derived volatiles, a clear antioxidant activity of chitosan was observed, which limits the release of these compounds, mainly aldehydes (hexanal and nonanal). Finally, the sensory analysis indicated that, although chitosan treatments received the lowest scores for all attributes, the reformulated samples did not differ from control sausages. Therefore, sausage containing chitosan may represent an interesting alternative for adding value to turkey meats affected by white striping myopathy and, at the same time, develop into a healthy and functional meat product increasing the proportion of fibers in one's diet.
Keywords: Pectoralis major; polysaccharide; meat product; healthy meat; functional food